The prevalence of Linguatula serrata nymphs in mesenteric and mediastinal lymph nodes in one-humped camels (Camelus dromedarius) slaughtered in Rafsanjan slaughterhouse, Iran - Bamorovat, Mehdi (Springer India, 2013)
Linguatula serrata is a well-known zoonotic parasite belonging to the order of Pentastomida which infects both human and animals. Human can be infected by both the nymph stage, causing a disease condition called nasopharyngeal linguatulosis or halzoun syndrome and the egg, a condition called visceral linguatulosis. The aim of this study was to evaluate the prevalence of nymphal stages of L. serrata in mesenteric and mediastinal lymph nodes of one-humped camels slaughtered in Rafsanjan slaughterhouse, Kerman province, south-eastern Iran. For this purpose, mesenteric and mediastinal lymph nodes of 132 one-humped camels of different sex and age groups in different seasons were examined. Overall, 27 one-humped camels (20.5 %) were infected by L. serrata nymphs. The infection rate increased with age (P < 0.05). No significant difference by sex groups or seasons was observed (P > 0.05). The high prevalence of infection in one-humped camels is of major concern to public health, owing to the zoonotic nature of the parasite and the potential risk of infection to humans and other animals.